The production of change: The social power in recuperated enterprises - Kasparian, Denise Romina (2022)
Worker-recuperated enterprises are experiences of social change in production. After over a decade of their spread and expansion in Argentina, this article takes stock of such experiences originated by the processes of worker-recuperated enterprises once they were consolidated, by posing the following question: To what extent does this form of “new cooperativism” imply social empowerment? Based on the comparative analysis of ten recuperated enterprises, we have characterised these enterprises with the aim of depicting potentialities and limitations regarding the dynamics of change and the growing social empowerment they portray. We suggest that recuperated enterprises represent a form of production which combines the control by the social power of associated workers with the competition in the capitalist market.